The Conference of the Birds : Miss Peregrine's Home for Peculiar Children Series #5 - Riggs, Ransom (New York : Dutton Books, 2020)
On a mission to deliver newly contacted peculiar Noor Pradesh to an operative known only as V, Jacob and his friends work feverishly to decipher the prophecy with only a few bewildering clues to follow while pursued by dangerous enemies.
Keywords: Supernatural -- Fiction; Fantasy